The Impact of educational intervention on attitude toward organ donation among health care workers in Malaysia - Wan Muhd Shukeri, Wan Fadzlina; Mazlan, Mohd Zulfakar; Kamaruzaman, Lydia; Budiman, Maryam; Mohamad Yusof, Aliza; Ramly, Nur Fariza; Nanyan, Suhaila; Wan Ali, Wan Ahmad Syahril Rozli; Abd Halim, Nurul Huda; Mohd Sharif, Nur Hidayati; Abdul Hafidz, Muhammad Iqbal (Elsevier Inc., 2022)
Background. The attitudes of the health care workers (HCWs) are essential in influencing organ donation rate. The aim of this study was to assess the effects of an educational intervention on attitudes toward organ donation among HCWs. Methods. A questionnaire-based interventional study was conducted with 458 HCW from 5 hospitals in Malaysia. A 26-item self-administered questionnaire was distributed online as a pre- intervention test. Respondents then went through website-based educational materials followed by a post-intervention questionnaire. Results. A total of 345 (75.3%) respondents completed the tests. Their attitude toward organ dona- tion was positive preintervention. After the intervention, respondents expressed an increase willingness to donate their own organs (P = .008) and their relatives’ organs (P < .001) after death; were more willing to adopt organ donation as part of end-of-life care (P =.002); were more comfortable talking to relatives about organ donation (P =.001); and expressed an increase consideration to execute the action at any time (P =.001). There was increased willingness to admit to the intensive care unit for facilitating organ donation (P =.007); to employ the same resources to maintain a potential brain-dead donor (P < .001); and to support organ donation in case they or their relatives were diagnosed with end-stage organ failure (P =.008). However, there was an increase in negative attitudes regarding the association between organ donation with health care failure (P =.004) and with pain (P =.003). Posi- tive attitude scores were higher after the intervention (P < .001). Conclusion. An educational website-based intervention was able to improve the attitudes of HCWs toward organ donation.